2022
DOI: 10.3390/metabo12030207
|View full text |Cite
|
Sign up to set email alerts
|

Sex-Specific Catabolic Metabolism Alterations in the Critically Ill following High Dose Vitamin D

Abstract: Pharmacological interventions are essential for the treatment and management of critical illness. Although women comprise a large proportion of the critically ill, sex-specific pharmacological properties are poorly described in critical care. The sex-specific effects of vitamin D3 treatment in the critically ill are not known. Therefore, we performed a metabolomics cohort study with 1215 plasma samples from 428 patients from the VITdAL-ICU trial to study sex-specific differences in the metabolic response to cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 72 publications
0
4
0
Order By: Relevance
“…Despite adjustment for sex, the results may be driven by unmeasured confounders related to differences between men and women. 70 Third, we also did not include an strictly independent replication cohort for these findings; however, we generalize this with observe consistent clinical findings to other time point during COVID-19 using an independent group of individuals, which does provide an initial form of validation of these findings. Finally, we extracted clinical data from EMRs; as this captures “real life” clinical data, outcomes measures and other clinical characteristics and are often incomplete.…”
Section: Discussionmentioning
confidence: 93%
“…Despite adjustment for sex, the results may be driven by unmeasured confounders related to differences between men and women. 70 Third, we also did not include an strictly independent replication cohort for these findings; however, we generalize this with observe consistent clinical findings to other time point during COVID-19 using an independent group of individuals, which does provide an initial form of validation of these findings. Finally, we extracted clinical data from EMRs; as this captures “real life” clinical data, outcomes measures and other clinical characteristics and are often incomplete.…”
Section: Discussionmentioning
confidence: 93%
“…These include a decrease in total 25(OH)D levels but no change in free 25(OH)D levels compared with healthy individuals and a spontaneous increase in vitamin D metabolites after the resolution of critical illness [61,62]. Furthermore, the difference in absorption and metabolic response between men and women was recently reported [63]. Finally, in a posthoc metabolomics study of the VITdAL-ICU trial, an increase of 25(OH)D more than 15 ng/ml after supplementation was associated with favourable changes in metabolites involved in endothelial protection, enhanced innate immunity and improved mitochondrial function.…”
Section: Vitamin Dmentioning
confidence: 99%
“…Sex differences have also been observed in high-dose VitD supplementation among critically ill men and women in a randomized placebo-controlled trial. In this study, women received higher doses of VitD than their male counterparts but showed significantly lower VitD absorption than males [ 63 ]. Additional research has shown sex-specific differences in coagulation and blood lipids during VitD intervention.…”
Section: Sex-specific Responsementioning
confidence: 99%
“…For instance, VitD enhances tolerance-inducing Treg populations, depresses B cell proliferation, reduces LPS-induced cytotoxicity, skews toward a Th2 response (over Th1, Th17, etc. ), and decreases numerous pro-inflammatory cytokines (MCP-1, IL-1, IL-2, IFN-γ, TNF-α, IL-17, IL-21, and iNOS) while boosting anti-inflammatory cytokines (IL-4, IL-10, and IL-13) [ 29 , 61 , 62 , 63 ]. Even in the absence of T2DM, excess adiposity (roughly estimated by BMI) elevates serum inflammatory markers (IL-6, TNF, and MCP-1) [ 67 , 72 ].…”
Section: Type 2 Oxidative Stress and Autoimmunitymentioning
confidence: 99%